An Overview of Hypoglycemia in Children Including a Comprehensive Practical Diagnostic Flowchart for Clinical Use - Casertano, Alberto; Rossi, Alessandro; Fecarotta, Simona; Rosanio, Francesco Maria; Moracas, Cristina; Di Candia, Francesca; Parenti, Giancarlo; Franzese, Adriana; Mozzillo, Enza (Frontiers in Endocrinology, 2021)
Hypoglycemia is the result of defects/impairment in glucose homeostasis. The main etiological causes are metabolic and/or endocrine and/or other congenital disorders. Despite hypoglycemia is one of the most common emergencies in neonatal age and childhood, no consensus on the definition and diagnostic work-up exists yet. Aims of this review are to present the current age-related definitions of hypoglycemia in neonatal-pediatric age, to offer a concise and practical overview of its main causes and management and to discuss the current diagnostic-therapeutic approaches. Since a systematic and prompt approach to diagnosis and therapy is essential to prevent hypoglycemic brain injury and long-term neurological complications in children, a comprehensive diagnostic flow chart is also proposed.